'A Veritable Mountain of Data and Years of Endless Statistical Manipulation': Methods in the Three Worlds and After. Issue 2 (15th December 2014) - Barrientos, Armando
Abstract : This article assesses the methodological contribution of Esping-Andersen's Three Worlds of Welfare Capitalism to welfare regime analysis. It revisits the methods deployed in the Three Worlds and assesses their influence on the practice of welfare regime researchers. It finds that welfare regime researchers have embraced the methods presented in the Three Worlds in a piecemeal fashion. Data reduction techniques, such as cluster and latent variable techniques, compete with index construction as the tools of choice for identifying clusters. Although regression analysis has been used extensively in linking welfare programme design and outcomes with welfare regimes, few researchers have followed Esping-Andersen in employing regression analysis in the context of linking policy and politics. Qualitative comparative analysis methods are increasingly employed by welfare regime researchers as an alternative. Finally, the article considers the methodological implications associated with extending welfare regime analysis globally.